Diversity of Marine Macro-Algicolous Endophytic Fungi and Cytotoxic Potential of Biscogniauxia petrensis Metabolites Against Cancer Cell Lines - Sahoo, Subhadarsini; Subban, Kamalraj; Chelliah, Jayabaskaran (Frontiers in Microbiology, 2021)
Hypersaline environments are known to support diverse fungal species from various orders. The production of secondary metabolites is one of the strategies that fungi adopt to thrive under such extreme environments, bringing up the stress tolerance response. Some such unique secondary metabolites also exhibit clinical significance. The increasing prevalence of drug resistance in cancer therapy demands further exploration of these novel bioactive compounds as cancer therapeutics. In the present study, a total of 31 endophytic fungi harbouring inside red, green and brown marine algae have been isolated and identified. The maximum likelihood analysis and diversity indices of fungal endophytes revealed the phylogenetic relationship and species richness. The genus Aspergillus was found to be the dominating fungus followed by Cladosporium spp. All the isolated endophytic fungal extracts were tested for their cytotoxicity against HeLa and A431 cancer cell lines. Nine isolates were further analysed for their cytotoxic activity from the culture filtrate and mycelia extract. Among these isolates, Biscogniauxia petrensis showed potential cytotoxicity with CC50 values of 18.04 and 24.85 µg/mL against HeLa and A431 cells respectively. Furthermore, the media and solvent extraction optimization revealed the highest cytotoxic active compounds in ethyl acetate extract from the potato dextrose yeast extract broth (PDYEB) medium. The compounds-induced cell death via apoptosis was 50–60 % and 45 % when assayed using propidium iodide (PI)-live/dead and loss of mitochondrial membrane potential (MMP) assay respectively in HeLa cells. Four bioactive fractions (bioassay-based) were obtained and analysed using chromatography and spectroscopy. This study reports, for the first time, cytotoxic activity from an endophytic fungal community that was isolated from marine macro-algae in the Rameswaram coastal region of Tamil Nadu, India. In addition, B. petrensis is a prominent apoptotic agent, which can be used in pharmaceutical applications as a therapeutic